Regulatory reinforcement, audit effort, and market perceptions of restatements - Yoon, Inkyung; Chung, Ju Ryum (The Economics and Finance Letters, 2025)
This study examines the changes in audit effort and financial restatements following the November 2018 amendment to the External Audit Act in South Korea. Using 2016–2022 as the sample period, it investigates whether restatements differentially affect the value relevance of earnings in the capital market. The findings indicate that the strengthened regulatory framework significantly increased audit effort, as measured by audit hours, total audit fees, and audit fees per hour, which, in turn, increased restatements. Before the External Audit Act was amended, the market interpreted restatements as negative signals, thereby reducing the value relevance of earnings. However, following regulatory reinforcement, such negative perceptions diminished, and this effect was more pronounced in firms with higher audit effort. These results suggest that investors distinguish between restatements stemming from managerial misconduct and those arising from enhanced audit scrutiny in a stricter regulatory environment. By highlighting the mediating role of increased audit effort in the relationship between regulatory reinforcement and financial restatements, this study provides insights into factors that influence the perceived reliability of financial disclosures. It offers implications for accounting standard-setters and policymakers concerned with the broader effects of strengthened regulations on audit practices and market perceptions.